235 Description of the context for injury prevention interventions development and implementation in youth Brazilian basketball: a cross-sectional study. (3rd March 2020) - Augusto Borges Gomes, Luiz; Andreoli, Carlos Vicente; Cunha, Ronaldo Alves da; Oliveira, Helena Santos de; Ejnisman, Benno; Cohen, Moises
Abstract : Background: The implementation of injury prevention interventions commonly do not consider the context where injury occurs. Objective: To describe the socioecological context to guide the development and implementation of injury prevention interventions in youth Brazilian basketball (YBB). Design: Cross-sectional study. Setting: YBB teams affiliated to the Basketball Federation of the State of São Paulo. Participants recruitment and data collection occurred during the regular season, between March and September 2018. Patients (or Participants): 534 athletes and 54 staff members of 35 YBB teams were included in the study. Eligibility criteria included (1) staff members who have graduated in a health care profession and (2) youth athletes with age between 10 and 19 years old. Interventions (or assessment of risk factors): Participants responded a survey on a regular day of practice or official match. Main outcome measurements: Athletes survey included personal information, training profile, knowledge about injury prevention and history of basketball-related musculoskeletal injuries over the last 3 months. Staff member survey included personal information, professional profile, team characteristics, knowledge about injury prevention, and preferences related to the development of an injury prevention program. Results: 52% (n=277) of youth athletes (12.2±1.7 years-old) and 21% (n=11) of staff members (sport experience: 17.1±9.5 years) never received any information about sports injury prevention interventions. 31.4% (n=11) of YBB teams do not perform injury prevention interventions with their athletes. Injury prevalence was 23.2% and the most common injury was ankle sprains (25.3%; n=40). Preferences related to the development of an injury prevention program included a program presented through a website, delivered by the physiotherapist within the daily warm-up routine. Conclusions: The majority of staff members had already received information about sports injury prevention interventions and YBB teams had already implemented injury prevention interventions with their athletes, but more than a half of athletes knew nothing about the topic. Additionally, information reported by athletes was frequently not evidence-based.